Towards cross-cultural knowledge through cross-indigenous methods and perspective - Enriquez, Virgilio G. (1979)
In pursuit of universal knowledge, social scientists have taken to cross-cultural methods in their research work. However, what is presently recognized as cross-cultural approach is merely the application of Western models in different settings. Although it broadens psychology's data base, it does not in any way lead the researcher nearer to his goal. If ever cross-cultural, universal knowledge is to be had, it must come out of the cross-indigenous method and perspective. The paper discusses the nature of cross-indigenous approach and evaluates its merits.
Includes bibliographical references (pages 14-15).